Combining ability estimates for quality and non-quality protein maize inbred lines for grain yield, agronomic, and quality traits - Amegbor, Isaac Kodzo; van Biljon, Angeline; Shargie, Nemera Geleta; Tarekegne, Amsal; Labuschagne, Maryke T. (Frontiers in Sustainable Food Systems, 2023)
Biofortified maize varieties could contribute to the fight against hunger and malnutrition of the increasing human population and help meet the high demand of maize for human consumption, industrial use and feed for animal and poultry. The understanding of the genetic mechanisms conditioning the inheritance of grain yield and other agronomic and quality traits is essential in the development of superior maize genotypes. The main objective of this study was to determine the combining ability for grain yield and other agronomic traits of QPM and non-QPM inbred lines crossed with two QPM and two non-QPM testers. A total of 130 hybrids were obtained by crossing 10 non-QPM and 23 QPM lines with four elite testers (two QPM and two non-QPM). The 130 single cross hybrids were evaluated at 13 sites in 2018 and 2019. The results showed significant general combining ability (GCA) for lines and testers as well as significant specific combining ability (SCA) for hybrids for most of the measured traits. Non-additive gene action controlled the inheritance of grain yield while agronomic and quality traits were controlled by additive gene action. QPM lines 11, 14 and 28 and non-QPM tester CML444 showed desirable GCA effects for grain yield, indicating that these lines in combination with tester CML444 should be considered when targeting development of superior maize genotypes with QPM traits. Based on the SCA values, crosses 120, 108, 105, 99, 85 and 41 were identified as the best hybrids across the locations. It is recommended that maize breeding programs targeting the development of high yielding QPM hybrids should exploit QPM lines with high GCA values for heterosis to be realised. In addition, the identified superior hybrids may be further evaluated and consequently promoted for commercial release which could increase incomes of farmers and help to alleviate poverty, hunger and malnutrition in southern Africa and sub-Saharan Africa at large.